El teatro infantil para mejorar la expresión corporal de las niñas y niños de 5 años del primer grado de la Unidad Educativa Militar Nº. 5 Lauro Guerrero de la Ciudad de Loja. Periodo 2014-2015 - Sigcho Poma, Ximena del Rocío (2016)
The present research work titled: THE CHILD THEATER TO IMPROVE THE BODY EXPRESSION OF THE DE GIRLS AND BOYS OF 5 YEARS OLD OF THE FIRST GRADE OF THE LAURO GUERRERO MILITARY ELEMENTARY Nº. 5 SCHOOL OF THE LOJA CITY. PERIOD 2014-2015 . In the present research work he/ she suggested a general objective: Determine the importance of the Child Theater to improve the Corporal Expression of the girls and boys of 5 years old of the first grade of the Lauro Guerrero Military Elementary No. 5 School of the Loja city. Period 2014-2015. The methods used in the elaboration of the present research work were: the Scientist, Deductive-inductive, Analytic-synthetic, the Statistical and the Descriptive one. The techniques and applied instruments were: the survey for the teachers and the observation guide to the 10 girls and the 20 boys 5 year-old, whose application was in an individual way and the purpose was to determine the development of the body expression, for this way to be able to observe the second variable. Obtaining of this way the following results: the 2 teachers that correspond to 100%, said that the child theater improved the body expression in the boys and girls. Of the total of girls and boys considered to determine the level of development of the body expression that they were 30 and that they correspond to 100%, 10 girls correspond to the 33% and 20 boys correspond to 67% which it allows to deduce clearly that the boys overcome to the girls statistically. Between the main results of the research work it can describe the 97% of girls and boys already have a level of development of corporal expression acquired and for this it is recommended that the teachers should select activities or learning situations that it allows them to develop imitation, dramatization and expression abilities